2007
DOI: 10.2106/jbjs.f.01224
|View full text |Cite
|
Sign up to set email alerts
|

Locking Compression Plate Fixation of Vancouver Type-B1 Periprosthetic Femoral Fractures

Abstract: On the basis of the high failure rate in this series of patients, locking compression plates do not appear to offer advantages over other types of plates in the treatment of type-B1 periprosthetic femoral fractures. Despite the potential to preserve the cement mantle, the locked screws did not appear to offer good pullout resistance in this fracture type. We believe that supplementation with strut allografts should be used routinely if this type of locking compression plate is selected to treat these fractures. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…No cases of nonunion were seen in survivors with at least 6 months of follow-up. This is in line with the results of Chakravarthy et al (2007), who reported union in 10 of 11 type B1 or type C PFFs in THR treated with a locking plate, but it contrasts with the results of Buttaro et al (2007), who reported union in 8 of 14 type B1 or type C PFFs in primary and revision THR.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…No cases of nonunion were seen in survivors with at least 6 months of follow-up. This is in line with the results of Chakravarthy et al (2007), who reported union in 10 of 11 type B1 or type C PFFs in THR treated with a locking plate, but it contrasts with the results of Buttaro et al (2007), who reported union in 8 of 14 type B1 or type C PFFs in primary and revision THR.…”
Section: Discussionsupporting
confidence: 84%
“…Fourthly, the ratio of males to females was 1:3, and the median age at PFF surgery was 78 years, which is comparable to that reported in other studies on PFF in primary and revision THR. Thus, we have no reason to believe that there was bias regarding sex and age (van der Wal et al 2005, Buttaro et al 2007, Charkravarthy et al 2007, Zuurmond et al 2010). Lastly, Lindahl et al (2006) described no difference in the outcome of PFF between cemented and cementless stems; thus, both types of fixation were included.…”
Section: Discussionmentioning
confidence: 99%
“…Second, loss of the proximal femoral cancellous bone was of concern while removing the thrust plate because of enhanced bone growth on the surface of the thrust plate [6]. Finally, the subtrochanteric fracture was a transverse fracture, and stability and bone union of such fractures are difficult to obtain [20]. Considering these problems, we planned revision surgery with a long distally fixed intramedullary stem in conjunction with a plate and cable system.…”
Section: Discussionmentioning
confidence: 99%
“…A risk factor for this is revision surgery, which can devitalise periosteum and local soft tissue, leading to poor blood supply. These factors contribute to an increased risk for delayed union, nonunion and infection [23]. In an attempt to limit further periosteal damage, this study used locked-plate constructs.…”
Section: Discussionmentioning
confidence: 99%